Designing Fashion Product with Natural Material and Purple Sweet Potato Peel Dye - Yunita Fitra Andriana; Hapiz Islamsyah (Jurnal Desain, 2023)
The fashion industry is one of the industrial sectors that produces the highest levels of pollution in the world, through waste that can pollute the air, water and soil. Pollution also occurs when the product's lifecycle is ended. When fashion products are no longer used, there will be a huge amount of waste that is difficult to decompose. During the COVID-19 pandemic, public awareness of environmental sustainability has increased. Therefore, an alternative fashion product that is more environmentally friendly is needed. The use of natural materials and dyes is one step in producing eco-friendly alternative fashion products. In this study, the natural dye explored and analyzed was purple sweet potato peel extraction, which was applied to silk fabrics. This research is qualitative research with experimental methods. The fashion products produced are dresses with simple cuts that can be worn on various occasions, semi-formal or formal. In addition, a simple dress cut is expected to have a longer use lifetime, because it does not refer to a particular trend.